Hydrogenation of (Zr69.5Al7.5Cu12Ni 11)100 - XTix quasicrystalline alloys and its effect on their structural and microhardness behavior - Singh D.; Shahi R.R.; Yadav T.P.; Mandal R.K.; Tiwari R.S.; Srivastava O.N. (My University, 2025)
The present study deals with the microstructural changes with respect to the addition of Ti and their correlation with hydrogen storage characteristics of (Zr69.5Al7.5Cu12Ni11) 100 - xTix (x = 0, 4 and 12) quasicrystalline alloys. The grain size of quasicrystals decreases with addition of Ti. It has been found that the alloy with x = 0 absorbed 1.20 wt. %, whereas the alloys with x = 4 and 12 absorbed 1.38 wt. % and 1.56 wt. % of hydrogen respectively. Hydrogenation was found to exhibit a significant effect on the structure/microstructure and microhardness behavior of (Zr69.5Al7.5Cu 12Ni11)100 - xTix quasicrystalline alloys. Variation in the microhardness behavior has been discussed based on a structure-property correlation. © 2013 Elsevier B.V.